Publizistische Freiheit und Persönlichkeitsschutz - zu den Grenzen der Verwertbarkeit realer Biografien - Martin, Marc-Oliver (Universitätsverlag Göttingen, 2008)
Publishing of diaries and biographies is a lucrative business, fictional texts are always looking close to real people and events that a market for the "sale" of life stories has become established. The development of law against this practice is fallen behind. The present study focuses on two questions circles. The first focus is on the systematization of the decision parameters and the derivation of concrete responses from the basics of intellectual property law.